2019
DOI: 10.1016/j.ijnss.2019.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Sources and symptoms of stress among nurses in the first Chinese anti-Ebola medical team during the Sierra Leone aid mission: A qualitative study

Abstract: Objective This study investigated the sources of stress, corresponding symptoms, and stress relief among nurses of the first Chinese anti-Ebola medical team during the Sierra Leone aid mission. Method A purposive sampling method was used and 10 nurses were selected from the first Chinese anti-Ebola medical team that was dispatched to Sierra Leone. Data were collected via phone and semi-structured interviews, then analyzed using Colaizzi's seven-step method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 15 publications
5
50
0
2
Order By: Relevance
“…In line with what we have found, health workers had high prevalence rates of severe insomnia, anxiety, depression, somatization, and obsessive-compulsive symptoms during the ongoing COVID-19 pandemic, as reported in several studies [3-6, 15, 20].This was also evident with previous outbreaks such as that of SARS and MERS-Cov [21][22][23][24]. The reluctance of hospital workers to participate in our study as observed by the lower response rate could be also interpreted as a reflection of their low mood.…”
Section: Discussionsupporting
confidence: 90%
“…In line with what we have found, health workers had high prevalence rates of severe insomnia, anxiety, depression, somatization, and obsessive-compulsive symptoms during the ongoing COVID-19 pandemic, as reported in several studies [3-6, 15, 20].This was also evident with previous outbreaks such as that of SARS and MERS-Cov [21][22][23][24]. The reluctance of hospital workers to participate in our study as observed by the lower response rate could be also interpreted as a reflection of their low mood.…”
Section: Discussionsupporting
confidence: 90%
“…In line with what we have found, health workers had highprevalence rates of severe insomnia, anxiety, depression,somatization, and obsessive-compulsive symptoms during the ongoingCOVID-19 pandemic, as reported in several studies (3-6, 15,20-21).This was also evident with previous outbreaks such as thatof SARS and MERS-Cov (22)(23)(24)(25). The reluctance of hospital workers toparticipate in our study as observed by the lower response ratecould be also interpreted as a re ection of their low mood.Interestingly, contrary to what have been reported, the level ofpsychological distress did not differ between medical andnon-medical hospital workers in our survey (15).…”
Section: Discussionsupporting
confidence: 90%
“…This situation had a significant impact on the physical and mental wellbeing of frontline healthcare workers, who were under increasing daily pressure for prolonged work shifts, scarcity of personal protective equipment, fear of being infected and of infecting their own family members ( Lancet, 2020 ), and for the stress associated with the loss of many patients, colleagues and in some cases of their loved ones ( Zaka, Shamloo, Fiorente, & Tafuri, 2020 ). Some studies have shown that, when in close contact with patients with emerging infectious disease, including SARS ( Chung, Wong, Suen, & Chung, 2005 ), MERS-Cov ( Kim, 2018 ), Ebola ( Van Bortel, Basnayake, & Wurie, 2016 ) ( Liu, Wang, & Zhou, 2019 ), H1N1 ( Honey & Wang, 2013 ), Clinical Staff (CS) can suffer from loneliness, anxiety, fear, fatigue, sleep disorders, which are likely to result in a poorer quality of healthcare for patients ( Su, Weng, & Tsang, 2009 ). What is more, long-term psychological consequences are also likely to be brought about, including higher levels of burnout, psychological distress and post-traumatic stress disorder.…”
Section: Introductionmentioning
confidence: 99%